Changes with Age in Amino Acids and some Mineral Constituents of Worker Honeybees. - El-Shakaa, S. M. A.; Shahein, Ali (Contributions to Entomology = Beiträge zur Entomologie, 1989)
The protein content, amino acid composition and minerals of worker honeybee that sampled every 5 day intervals until 20 days old. The nitrogen and mineral contents during the early life of a bee were high and declined with age. Total protein content ranged from 41,3% in worker bees 20 days old to 69% in newly emergence. Results of amino acid analyser indicated that glutamic acid was the predominant amino acid in all samples, except 5 days old bees that alanine was considered the highest one. Cystine was considered the lowest amino acid with no appreciable differences in worker bees during different ages. The mineral constituents of bees generally decline with age. The higest total mineral contents appeared in newly emergence (3,93%) and decreased gradually until reached a minimum in 20 days old bees (1,60%). Potassium and phoshorus are the most abundant mineral constituents of worker bees. Sodium, calcium, magnesium and iron are present in considerably smaller quantities. Zinc and manganese remain relatively constant during different ages, except the latter very low in 10 days old bees. Copper was the lowest mineral content in all samples. The preliminary data indicate that the changes in the protein content and mineral constituents of honeybees are probably connected with their activities or the division of labor.